Carbon monoxide stable isotope data from laboratory heating experiments and collection of air from Stony Brook, NY, on Long Island, 2019-2022 - Gregory A Henkes; Philip F Place; John E Mak (PANGAEA, 2024)
Clumped isotope data of carbon monoxide (analyzed as CO oxidized to CO2) from laboratory heating experiments and collections of natural air samples from the campus of Stony Brook University from 2019-2022. Air sampling was done from the School of Marine and Atmospheric Sciences building roof (Dana Hall), see doi:10.1594/PANGAEA.971624. Laboratory heating experiments equilibrated CO in tube furnaces at elevated temperatures 300-1000 °C for periods of hours to days. These heating experiments were done (1) in the presence of platinum wire, (2) by the reaction of graphite with CO2, and (3) by the decomposition of calcium carbonate in the presence of Zn metal.
In: Henkes, GA et al. (2024): Carbon monoxide stable isotope data from laboratory heating experiments and collection of air from Stony Brook, NY, on Long Island [dataset bundled publication]. PANGAEA, https://doi.org/10.1594/PANGAEA.971623